Prediksi Distribusi Air Perusahaan Daerah Air Minum (PDAM) Tirta Dharma Kota Pasuruan Menggunakan Metode Jaringan Syaraf Tiruan Backpropagation - Agustina, Dwi; Hafiyusholeh, Moh.; Fanani, Aris; Prasetijo, Dono (LPPM Universitas Dinamika Bangsa, 2023)
Every human being has the right to use clean water which is the most important resource for daily needs. The author wants to predict PDAM water distribution using the backpropagation neural network method, so that it can help PDAM Tirta Dharma Pasuruan city to find out the estimated water distributed to customers for the next period. This research was conducted using water distribution data obtained directly from PDAM Pasuruan City from January 2019 to December 2021. The architectures used in this study are 4-2-1, 4-4-1, and 4-8-1, with architectures the best is 4-2-1, which has an accuracy rate of 100%, a learning rate of 0.1, a target error of 0.001, and a maximum epoch of 1000. The number of predictions for the distribution of water in PDAM Tirta Dharma, Pasuruan City in 2022 was 6,829,056, in 2023 there were 6,865. 358, in 2024 there will be 6,867,817, and in 2025 there will be 6,868,785.